DEVELOPMENT OF TOURISM IN KARAKALPAKSTAN ON THE BASIS OF DIGITAL TECHNOLOGIES - Matyakupova Madina Quzibay qizi (Web of Journals Publishing, 2025)
This article analyzes the current state of the tourism sector in the Republic of Karakalpakstan and considers the possibilities of developing tourism services using digital technologies. The article pays special attention to the types of digitization, advanced foreign experiments and the possibilities of their application to the conditions of Karakalpakstan.
Keywords: Tourism, digital technology, digitization, smart Tourism, Information Systems, online services.